Efectiveness of Kursus Asas Keusahawanan Siswa on University graduate intention in becoming agri-entrepreneurs - Muhammad Mu'az, Mahmud (2013)
The effort of promoting agri-entrepreneurship in Malaysia has been pertinacious. This is parallel with the vision of the nation which is going through transformation towards becoming a developed country. Students are exposed as early as primary school to entrepreneurial subjects and related learning. A huge amount of investment is made by the government to develop this sector. Many courses and trainings were conducted to achieve the target of developing more entrepreneurs especially among graduates, thus making individuals more aware of this issue. Some universities also require students to take up entrepreneurial subjects regardless of their academic programmes. However, the effectiveness of these courses and trainings are debateable. This study intends to uncover the underlying factors that could influence the intentions of KAKS graduates to take up agriculture as an agribusiness activity as a career. The Theory of Planned Behaviour (TPB) was adopted as the theoretical framework for this study. In total, 1005 respondents who had participated in KAKS were interviewed through completing a structural questionnaire which gathered information on their social attitude towards the effectiveness of KAKS course and their intention of becoming an agri-entrepreneur. Chi-square analysis was employed to determine the relationship between socio-economic and demographic factors towards participants being motivated by KAKS course and the development of entrepreneurial skills and traits among KAKS participants. For the first chi-square analysis, the results indicate that most of the socio-economic and demographic factors such as state of origin of respondents, entrepreneurial status of KAKS participants, family members involved in entrepreneurship and having agricultural family background have significant differences with the degree of motivation produced with the KAKS course. For the second chi-square analysis, the results indicate that some of the variables of demographic factors such as availability of family members in entrepreneurships, having agricultural family background and educational background have significant differences with the development of agri-entrepreneurial skills among KAKS participants. Exploratory Factor Analysis was used to uncover the underlying factors that could influence the intentions of graduates (KAKS course participants) to take up agriculture as an agribusiness activity in their career. There are 5 factors identified as latent factors influencing KAKS participant regarding the course and their intention to become an agri-entrepreneurs. The 5 factors comprises of motivation, cognizance of KAKS course, society'S influence, personal goal setting and risk taking. Binary logistic model procedure was applied to determine the extent to which selected socio-economic/demographic characteristics and attitudes and also factors that influence the intentions of KAKS participants in becoming agri-entrepreneurs affected their influence on KAKS program itself. The results indicated that, the socio-economic variables such as availability of family members in entrepreneurship, state of origin of participants and educational background play an important role when explaining the influence of KAKS course on participants. Besides that, factors that influence the intentions of KAKS participants in becoming agri-entrepreneurs such as motivation, cognizance of KAKS course and society's influence also play an important role towards the influence the participants have on KAKS. KAKS has been proven to be successful in terms of developing interest among its participants to become an agri-entrepreneur. Though, motivation is a very important factor towards influencing KAKS participants to become agri-entrepreneurs. These courses are very helpful especially for graduates who want to become agri entrepreneurs but do not have the basic of entrepreneurial knowledge. The role of family members is also very influential towards the decision of graduates to become agri-entrepreneurs. Though participants of KAKS from technical backgrounds and graduates from East Coast and Northern Region states are more prone in becoming agri-entrepreneurs, participants from non-technical backgrounds and other states besides East Coast and Northern Region states are also positively influenced by KAKS course. This indicates that KAKS is able to influence all graduates from any background to become agri-entrepreneurs.